Recommendation domains to scale out climate change adaptation in cocoa production in Ghana - Bunn, Christian; Läderach, Peter R.D.; Quaye, Amos; Sander, Muilerman; Noponen, Martin R.A.; Lundy, Mark M. (Elsevier, 2019)
Climate change is threatening cocoa production in West Africa and guidance towards site-specific adaptation is required. We developed recommendation domains with common degree of impact requiring incremental, systemic or incremental adaptation effort to provide decision support for interventions to scale out adaptive practices. We used Random Forests to divide the cocoa production belt into four zones with distinct climatic features under current and future climate conditions. To make model results actionable we used an expert validation approach. Cocoa experts evaluated and verified cocoa occurrence data for model input, prioritized climate and soil variables for modeling use and confirmed the validity of the distribution of climate zones.